Eco_Language: Edukasi Bank Sampah Berbasis Literasi Bahasa dan Teknologi pada Masyarakat Desa - Genisa, Risma Asriani Azis; Nihaya, Musdalifah; Sapan, Amika; Taufik, Muhammad Taufik; Yaumi, Muhammad Taufik Al Hakim; Absri, Absri (ADPERTISI, 2025)
The coastal village of Boddia in Takalar Regency faces increasing waste pollution due to the community’s limited awareness of sustainable waste management. To address this issue, a community service initiative was implemented using the Eco-Language approach, which integrates language and technology literacy in educating residents through the establishment of a local waste bank. The program involved several stages: awareness-building sessions, training in waste-based product creation, digital marketing workshops, and the development of a community waste bank structure. Actively involving local residents, the program succeeded in enhancing environmental awareness, fostering practical skills, and generating marketable products. Collaboration between academics and local authorities played a crucial role in shaping a mindset shift toward circular economy practices. The outcomes suggest that this model holds strong potential for adaptation in other coastal areas facing similar environmental challenges.